Beispiel Nr: 12
$ \text{Gegeben: } \\ p_1: y=a_1x^{2}+b_1x+c_1 \qquad p_2: y=a_2x^{2}+b_2x+c_2\\ \text{Gesucht:Schnittpunkte zwischen 2 Parabeln} \\ \text{Parabel-Parabel}\\ \textbf{Gegeben:} \\ p_1: y= 2x^2+3x+4 \qquad p_2: y= 5x^2+6x+7 \\ \\ \textbf{Rechnung:} \\f\left(x\right)= 2x^2+3x+4\qquad g\left(x\right)= 5x^2+6x+7\\ \bullet \text{Schnittpunkte zwischen zwei Funktionen} \\ f\left(x\right)=g\left(x\right) \\ 2x^2+3x+4= 5x^2+6x+7 \\ 2x^2+3x+4-( 5x^2+6x+7)=0\\ \begin{array}{l|l|l} \begin{array}{l} \text{a-b-c Formel}\\ \hline -3x^{2}-3x-3 =0\\ x_{1/2}=\displaystyle\frac{+3 \pm\sqrt{\left(-3\right)^{2}-4 \cdot \left(-3\right) \cdot \left(-3\right)}}{2\cdot\left(-3\right)}\\ x_{1/2}=\displaystyle \frac{+3 \pm\sqrt{-27}}{-6}\\ \text{Diskriminante negativ keine Lösung} \end{array}& \begin{array}{l} \text{p-q Formel}\\ \hline \\ -3x^{2}-3x-3 =0 \qquad /:-3 \\ x^{2}+1x+1 =0 \\ x_{1/2}=\displaystyle -\frac{1}{2}\pm\sqrt{\left(\frac{1}{2}\right)^2-1} \\ x_{1/2}=\displaystyle -\frac{1}{2}\pm\sqrt{-\frac{3}{4}} \\ \text{Diskriminante negativ keine Lösung} \end{array}\\ \end{array}\\ $